PENGARUH SALES CALL, EFFECTIVE CALL DAN SKU SOLD TERHADAP PENINGKATAN PENJUALAN SALESMAN UD. PRIMA JAYA MANDIRI (DIST. PT. NESTLE INDONESIA) - Sapri M Yahya; Rini Indahwati; Muhammad Fauzan Azhmy (STKIP Subang, 2026)
This study aims to analyze the effect of Sales Call, Effective Call, and SKU Sold on increasing sales performance of salesmen at UD. Prima Jaya Mandiri, a distributor of PT. Nestlé Indonesia in Gorontalo Province. The rapid development of business competition requires companies to implement effective marketing communication strategies and efficient inventory management to maintain sales growth. This research employed a quantitative research method with a descriptive statistical approach. The population consisted of consumers of UD. Prima Jaya Mandiri in Gorontalo Province, with a sample of 30 respondents selected using purposive sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, partial (t-test), and simultaneous (F-test) hypothesis testing. The results indicate that Sales Call, Effective Call, and SKU Sold each have a positive and significant effect on sales improvement partially. Simultaneously, these three variables also show a positive and significant influence on increasing sales performance. The findings suggest that effective personal selling communication, successful transaction outcomes, and accurate inventory control through SKU management play an important role in enhancing sales performance. Therefore, companies are encouraged to strengthen sales call strategies, improve communication effectiveness, and optimize inventory management to achieve sustainable sales growth.